Technological Pedagogical Content Knowledge in the literature: how TPCK is defined and implemented in initial teacher education - Marina De Rossi; Ottavia Trevisan (Italian Journal of Educational Technology, 2018)
In recent decades, there has been increasing research interest in teachers’ competences regarding the growing role of technologies in educational practices. These competences are grounded on a clear base of technological knowledge, along with the recognized dimensions of a broad pedagogical expertise and deep knowledge of the content. This paper analyses the most significant international literature on the topic, reporting the theoretical discussion about teachers’ knowledge as described by the Technological Pedagogical Content Knowledge framework (TPCK – Koehler & Mishra, 2005a) based on Shulman’s (1986, 1987) PCK. This framework will be analysed in its definition and main components, as well as in the different interpretations given by researchers in recent years. Finally, some of the main strategies documented in the literature to develop this type of teacher knowledge in pre-service education will be presented.